Teaching science in outreach programs may enhance health science communication and engagement in medical students - Prabhakar, Shruthi; Chang, Brianna S.; Rau, Kristofer K.; Carvalho, Helena (Frontiers in Communication, 2025)
Medical education increasingly emphasizes the development of communication, empathy, and teaching skills alongside scientific knowledge. Community outreach programs offer a unique opportunity for medical students to cultivate these competencies in real-world settings. This pilot study investigates the impact of participation in science outreach programs on the engagement and perceived professional development of medical students. Thirty medical students from the Virginia Tech Carilion School of Medicine volunteered in two community-based outreach programs—Kids’ Tech University (KTU) and Medical Discovery of Careers (MedDOCs). These programs involved interactive, hands-on teaching of physiological concepts to middle and high school students. Engagement levels were assessed using a modified Utrecht Work Engagement Scale (UWES), comparing students’ self-reported experiences during teaching versus studying. Thematic analysis was applied to qualitative reflections. Students reported significantly higher engagement scores while teaching compared to studying (5.8 ± 0.1; 4.4 ± 0.1) on a 7-point Likert scale, p < 0.05. Thematic analysis revealed four key themes: community engagement and social responsibility, personal and professional growth, educational creativity and communication skills, and inspiration through role modeling. Participation in community outreach programs may enhance medical students’ engagement, communication skills, and sense of purpose. These findings support the integration of structured outreach opportunities into medical education to foster holistic professional development.